PERAN GURU DALAM PENANAMAN NILAI-NILAI AKHLAQ PELAJARAN SEJARAH KEBUDAYAAN ISLAM PADA SISWA KELAS VII SMPIT AT-TAUBAH KARAWANG - Rosita Rahman; Sya’roni Ma’shum; Hinggil Pratama (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2022)
Instilling the values of akhlaq in modern times is something that should find more concern, considering that lately the decline of akhlaq is often intertwined, not only in people of age but also in young people let alone until childhood. This can be seen from the complaints of some parents, residents and people who are located in the school area, that the deterioration of akhlaq also took place in the students. Materially, the lessons of Islamic History are stories of the past, but the scope is not as narrow as what is in the discourse. It is a culture that is widely reflected in art, literature, religion and even morals. In the study of Islamic Cultural History often a teacher does not connect between learning materials with the purpose of learning. A teacher enters the classroom and then immediately tells or dictates the story of history. Teachers forget that a learning activity conducted in the classroom is a learning that has a clear purpose. The purpose of a teacher in carrying out learning is not only to improve the hours of the subjects, but to invite students to develop the intelligence that the learners have. On the other hand, learning will be formed in students a positive change, be it from the development of knowledge, skills, and attitudes or behaviors that arise after the learning process. In connection with this problem, the author wants to examine "The Role of Teachers in Instilling The Values of Akhlaq Mapel History of Islamic Culture in Grade Vii Students of SMPIT At-Taubah Karawang."